Development of novel hydrophobic hollow fiber membranes intended for gas-liquid membrane contactor application - Zhang, Yuan (2013)
This thesis presents the development of novel hydrophobic hollow fiber membranes intended for the use in gas-liquid membrane contactor (GLMC) application. GLMC process has been gaining popularity in recent years as a potential alternative for CO2 separation from various gas streams, such as biogas, natural gas, and flue gas. However, no commercial CO2 removal process using GLMC technology is presently in operation. The main technical barrier is membrane wetting. Hence, this study aims at developing highly hydrophobic and efficient porous hollow fiber membranes with strong chemical resistance for GLMC application. Overall, the hydrophobic hollow fiber membranes with controlled pore structures were prepared by the novel surface modification approaches and through the formation of highly hydrophobic inorganic-organic composite membranes. This study proves the important role of membrane engineering in terms of fabrication and modification techniques in facilitating commercialization of GLMC application.